Spike and Local Field Synchronization Between the Pedunculopontine Nucleus and Primary Motor Cortex in a Rat Model of Parkinson's Disease. (15th April 2019) - Geng, Xiwen; Wang, Xuenan; He, Feng; Zhang, Xiao; Xie, Jinlu; Gao, Guangheng; Han, Hongyu; Yao, Xiaomeng; Zhang, Haiyan; Gao, Yunfeng; Wang, Yanan; Wang, Min
Abstract: The pedunculopontine nucleus (PPN) shows altered electrophysiological and anatomic characteristics in Parkinson's disease (PD), but little is known about the effect of 6-hydroxydopamine (6-OHDA) lesion and levodopa (L -DOPA) therapy on the relationship between spike and local field potential (LFP) activities in the PPN and motor cortex. Aiming to investigate this, synchronous spike and LFP signals in the PPN and primary motor cortex (M1) were recorded. The spike–LFP relationship was evaluated using coherence analysis, phase-lock and spike-field coherence (SFC). The results suggested that 6-OHDA lesion had a significant effect on the spike–LFP relationship between the PPN and M1 in rats under a rest or locomotion state. The significantly altered frequency bands varied across different neuron types and animal activity states. In addition, the altered coherence values between PPN spike and M1 LFP were refractory to long-termL -DOPA therapy although all other changes could be reversed by this drug treatment. All results provided evidence of the spike–LFP relationship between the PPN and M1 in PD, revealing some network mechanisms of the cortico-basal ganglia circuitry and PPN, which might be an underlying candidate for PD pathophysiology and therapy. Highlights: 6-OHDA lesion in SNc had effect on spike–LFP coherence between PPN and M1 in rats. Distinct neuron types in PPN and M1 showed different spike–LFP coherence alteration. In spike–LFP coherency between PPN and M1, L -DOPA has a therapeutic limitation.